2013
DOI: 10.5539/elt.v6n7p9
|View full text |Cite
|
Sign up to set email alerts
|

Writing Error: A Review of Interlingual and Intralingual Interference in EFL Context

Abstract: This paper aims to review the theoretical concept of interlingual interference of the mother tongue, Thai to the target language, English and intralingual interference found in EFL student writing in Thai context with the attempt to define the existence of errors according to their sources. This review article also exemplifies some frequent errors normally found in Thai student writing based on three perspectives of interlingual interference; lexical, syntactic and discourse interference and seven aspects of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 21 publications
8
54
0
1
Order By: Relevance
“…They found that students' NL influenced their English writing. TL influence found in this study also includes both lexical and grammatical aspects, and this corresponds to the findings of Falhasiri et al (2011), Qaid (2011, Kaweera (2013), and NaPhuket (2015). They found various instances of intralingual error, ill-forms of the TL use which were not traceable to their NL.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…They found that students' NL influenced their English writing. TL influence found in this study also includes both lexical and grammatical aspects, and this corresponds to the findings of Falhasiri et al (2011), Qaid (2011, Kaweera (2013), and NaPhuket (2015). They found various instances of intralingual error, ill-forms of the TL use which were not traceable to their NL.…”
Section: Discussionsupporting
confidence: 89%
“…This is one of the main sources for the IL production in this study. A similar problem was found in the studies of Kaweera (2013) and Na-Phuket (2015) in which the students' English writings were influenced by their NL, resulting in interlingual errors, whereas the learning strategies used to deal with the complexity of English resulted in intralingual errors. This is convincing that the students' reliance on the acquired language knowledge of NL and some of the TL provides us with information of their linguistic development and learning process.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Kaweera (2013), for example, concludes that there are two main sources of errors, namely interlingual interference and intralingual interference. The first one is a negative transfer of learners' first language.…”
Section: Sources Of Errorsmentioning
confidence: 99%